Discovery of novel antibiotics by metabolic engineering of Streptomyces soil bacteria - Tirkkonen, Heli (My University, 2023)
Antimicrobial resistance is a rapidly developing threat that has been estimated to kill 10 million people yearly by 2050. This underscores the urgent need for novel antibiotics that do not share cross-resistance with existing ones. Recently, tetracenomycins were discovered to bind to the ribosome at a distinct site within the polypeptide exit tunnel, exhibiting no cross-resistance with other classes of antibiotics. However, tetracenomycins also displayed cytotoxic effects on human cell lines, which prevents the use of currently existing tetracenomycins as antibiotics. The aim of this study was to develop novel antibiotics based on the tetracenomycin scaffold that would display improved specificity against bacterial ribosomes, while harboring low affinity towards human ribosomes to mitigate cytotoxicity issues. To achieve this goal, we cloned 22 different sugar biosynthetic pathways into a modified Streptomyces strain that harbored genes for production of the tetracenomycin aglycone moiety, 8-demethyl-tetracenomycin C. The strain also contained a promiscuous glycosyltransferase, ElmGT, which has been shown to be able to transfer various carbohydrates to the aglycone. This approach resulted in the production of ten glycosylated analogs of 8-demethyl-tetracenomycin C, which were detected through HPLC-MS analysis. Furthermore, eight glycosylated analogs were isolated and purified using a combination of chromatographic techniques, and their chemical structures were elucidated through HR-MS and NMR analysis. The glycosylation of 8-demethyl-tetracenomycin C successfully eliminated the cytotoxicity observed in the compounds when tested against human cancer cell lines. Additionally, it was observed that methylation of either the sugar moiety or the aglycone moiety increased cytotoxicity. The attachment of sugar moieties also significantly lowered the antibacterial activity and influenced the target specificity against bacterial strains. Future studies with a broader range of compounds, strains, or target-drug structures will be required to establish more comprehensive structure-activity relationships of tetracenomycins.
Keywords: antibiotics, Streptomyces, glycodiversification, metabolic engineering